PROFIL HAMBATAN PELAKSANAAN PEMBELAJARAN DAN HUBUNGANNYA DENGAN MOTIVASI DAN HASIL BELAJAR KOGNITIF SISWA KELAS X IIS PADA MATA PELAJARAN BIOLOGI PROGRAM PEMINATAN DI SMA NEGERI 4 PEKANBARU - Sihotang, Romaito; Fauziah, Yuslim; Febrita, Elya (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the barriers of implementation learning and its relationship with learning motivation and students cognitive learning outcomes on learning across the biology interest of class X IIS SMAN 4 Pekanbaru. This research was conducted in May-June 2018. The sample in this study amounted to 59 students determined based on purposive sampling techniques. The instrument consisted of barrier implementation of learning questionnaires, student learning motivation questionnaires and documentation of cognitive learning outcomes. The data obtained were analyzed using the correlation test product moment at the level of 5%, test of determination, and descriptive analysis. The results showed that the implementation of learning biology across the interests of class X IIS students of SMAN 4 Pekanbaru an average of 2.85 with criteria experiencing obstacles; then there is a significant relationship between the barriers to the implementation of learning with learning motivation of 0.477 with the medium category and obtained the coefficient of determination (r2) of 0.228 and there is a significant relationship between the barriers to the implementation of learning with cognitive learning outcomes of 0.406 with the medium category and obtained the coefficient of determination (r2) of 0.165. Based on the results obtained, it can be concluded that the implementation of biology learning across the interests of class X IIS SMAN 4 Pekanbaru has criteria for obstacles, there is a moderate relationship between the barriers to the implementation of learning with learning motivation and cognitive learning outcomes.Key Words: Barriers, Cognitive Learning Outcomes, cross biological interest , Learning Motivation